Respostas

2014-05-17T16:28:27-03:00
Sendo A e B as raizes da equacao 1,5x² + 0,1x=0,6 ,podemos entao afirmar que a²+b² é 

1,5x² + 0,1x - 0,6 = 0
a= 1,5
b= 0,1
c= - 0,6
Δ= b² - 4ac
Δ= (0,1)² -4(1,5)(-0,6)
Δ= 0,01 + 3,6
Δ= 3,61
se 
Δ > 0 
então
x = - b - + 
√Δ/2a
x' = -0,1 - √3,61/2(1,5)
x' = - 0,1 - 1,9/3
x' = -2/3

x" = - 0,1 +√3,61/2(1.5)
x" = - 0,1 + 1,9/3
x" = 1,8/3
x = 0,6

Sendo A e B as raizes da equacao 1,5x² + 0,1x=0,6 ,podemos entao afirmar que a²+b² é 

A = -2/3
B = 0,6
A² + B² =
(-2/3)² + (0,6)² =
4/9 + 0,36 = 0,804444...≡ 0,80 ≡ 0,8